Development of an aircraft load planning system for distribution of passenger baggage - Awang Jumat, Nurkhairunisa; Abdullah, Ermira Junita (Science Publishing Corporation, 2018)
Airplane has been widely used as transportation compared to ship or car due to the short time journey. This phenomenon contributes to high demand or airline network for many places around the world and resulted in more competition for the airline industry due to changes in economy and increase in number of airlines. Besides, the increase in price of fuel can also be a major burden to the airline to maintain or gain profit. In order to overcome the fuel and cost problem, few measures can be taken including implementing effective aircraft loading system to optimize fuel weight and manage centre of gravity (CG), an aerodynamically clean aircraft, flight planning based on good data and optimal use of systems for example bleed, flaps and gear. For this study, load planning system for a Boeing 737-800 aircraft is considered to obtain a good position of CG for better fuel consumption. A load planning system was designed and developed using LabVIEW 2016 which can easily be integrated with sensors to produce a complete system. This system capable of receiving baggage weight as input and arranging the baggage to ensure the CG location is within the stipulated range. The efficiency of this system was validated by testing an aircraft model inside a wind tunnel and observing the performance of the aircraft when loads were arrange randomly and also based on the proposed arrangement by the system. As a result from the testing, by arranging the loads using the system that has been developed, a better flight performance in term of lift to drag ratio can be obtained which was 10.2 compared to randomly arranging the loads which was 7.9. Thus, by having a good load planning can reduce the fuel consumption and also improve the flight performance.